Constraints Analysis of MAHAGRAPES Farmers - Nikam Vinayak Ramesh , Premlata Singh , Shiv Kumar andRakesh E.S. (Indian Journal of Extension Education, 2014)
Mahagrapes is a marketing partner to a group of grape growers’ cooperative societies in Maharashtra. It helps grape growers in exporting their produce to European countries. The study was aimed at analysing constraints faced by Mahagrapes members during production and export of grapes. Nashik, Sangli and Pune districts of Maharashtra were purposively selected for data collection. Data were collected by focused group discussion and personal interview of members and constraints were ranked using Garrett’s ranking technique. The study revealed that major constraints faced by farmers were difficulty in following recommended practices, absence of produce procurement policy, lack of price policy for grapes by the Government, non-availability of labour during peak season and more incidence of pests and diseases.